Contextualization of Islamic Education Curriculum in Junior High Schools - Amir Maliki Abitolkha; Ahmad Nur Ismail; Yazid hady (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractSeveral years of experience teaching PLPG training for teachers in the Ministry of Religion, especially Islamic Religious Education (PAI) teachers, found the fact that